Long-Term Intrahost Evolution of Methicillin Resistant Staphylococcus aureus Among Cystic Fibrosis Patients With Respiratory Carriage - Azarian, Taj; Ridgway, Jessica P.; Yin, Zachary; David, Michael Z. (Frontiers in Genetics, 2019)
Staphylococcus aureus is the most commonly identified airway colonizer of cystic fibrosis (CF) patients, and infections with methicillin-resistant S. aureus (MRSA) are associated with poor outcomes. Yet, little is known about the intrahost evolution of S. aureus among CF patients. We investigated convergent evolution and adaptation of MRSA among four CF patients with long-term respiratory carriage. For each patient, we performed whole-genome sequencing on an average of 21 isolates (range: 19-23) carried for a mean of 1,403 days (range: 903-1,679), including 25 pairs of isolates collected on the same day. We assessed intrahost diversity, population structure, evolutionary history, evidence of switched intergenic regions (IGRs), and signatures of adaptation in the context of patient age, antibiotic treatment, and co-colonizing microbes. Phylogenetic analysis delineated distinct multilocus sequence type ST5 (n=3) and ST72 (n=1) clonal populations in addition to sporadic, non-clonal isolates, and uncovered a putative transmission event. Variation in antibiotic resistance was observed within clonal populations, even among isolates collected on the same day. Rates of molecular evolution ranged from 2.21-8.64 nucleotide polymorphisms per year, and lineage ages were consistent with acquisition of colonization in early childhood followed by subsequent persistence of multiple sub-populations. Selection analysis of 1,622 core genes present in all four clonal populations (n=79) found 11 genes variable in three subjects - most notably, ATP-dependent protease clpX, 2-oxoglutarate dehydrogenase odhA, fmtC, and transcription-repair coupling factor mfd. Only one gene, staphylococcal protein A (spa), was found to have evidence of gene-wide diversifying selection. We identified three instances of intrahost IGR switching events, two of which flanked genes related to quorum sensing. The complex microbial ecology of the CF airway poses challenges for management. We illustrate appreciable intrahost diversity as well as persistence of a dominant lineage. We also show that intrahost adaptation is a continual process, despite purifying selective pressure, and provide targets that should be investigated further for their function in CF adaptation.